Empowering Eco-Friendly MSMEs through Tax Management Education and Product Innovation in Palembang City - Nilam Kesuma; Nur Khamisah; Rizka Novelia; Sri Maryati (Indonesian Journal of Community Engagement, 2025)
This Community Service Program aims to empower environmentally friendly Micro, Small, and Medium Enterprises (MSMEs) in Palembang City through training on developing sustainable water hyacinth-based products and tax literacy education. The program was implemented using participatory methods such as field surveys, workshops, mentoring, and focus group discussions (FGDs). Participants were trained to process water hyacinth into environmentally friendly products with economic value and to manage their business finances and taxes more effectively. The results of the program showed a significant increase in participants' understanding of sustainable entrepreneurship and tax compliance, which contributes to environmental conservation and local economic growth. This program demonstrates that integrating tax management training with green innovation can strengthen the capacity of MSMEs towards sustainability and fiscal responsibility.